(3cJGH Gdage aj GdJUhas - (3HTQ Hf GdMGQKs
(3ChdgG (B:s
(3jHOC HHGH ePgH Cgd GdUahI ai Gdage hGdEJHGY hGdehGabg dcJGH Gddg YR hLd s
(3BNQgG (B:s
(3jfJgi HHGH ai PcQ ef ZdW ai GdQhM s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbHjIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJUha hGdBOGH GdTQYjIs